(untitled) (Semiárida, 2020)
This study includes a taxonomic review, based on exomorphological characteristics, of the genus Baccharis (Compositae) wich grows spontaneously in the province of La Pampa (Argentine). Twenty-three species have been identified; a key is provided in order to differentiate easily such taxa. No taxonomic novelties have been found, but for the first time, six species (Baccharis medullosa, B. cordobensis, B. neaei, B. spicata, B. triangularis and B. tridentata) and one variety (B. rufescens var. subrufescens) are mentioned for the Province of La Pampa.